PENGARUH ISLAMIC BRANDING, FASILITAS, DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN MENGINAP DI HOTEL SYARIAH WILAYAH KOTA BOGOR - Miftahul Janah (2022)
This study aims to explain the influence of Islamic branding, facilities, and service quality on the decision to stay at a sharia hotel in the Bogor City area. This research uses a quantitative method that refers to numerical data. The subjects studied were 150 guests who had been in sharia hotels in the Bogor City area. The object of his research was the decision to stay at a sharia hotel in the Bogor City Area. This study uses data analysis techniques used, namely descriptive statistical analysis, data quality, classical assumptions, multiple linear regression, and hypothesis testing. The results of this study are that Islamic branding does not have a significant influence on the decision to stay in sharia hotels, facilities have a significant influence on the decision to stay in sharia hotels, and the quality of service has an influence on the decision to stay in sharia hotels, and simultaneously Islamic branding, facilities, and quality of service have a significant influence on the decision to stay in sharia hotels. There is an influence of Islamic Branding, facilities, and quality of service in the decision to stay at Sharia Bogor hotel. With the contribution of this research, it can provide insight into consumer opinion on the use of Islamic brands ini halal tourism, especially towards Sharia hotels.